Efektivitas Penggunaan Media Sosial TikTok Untuk Pembelajaran Biologi di SMA Negeri 1 Rantau Utara - Arnisah, Miftaah; Harahap, Risma Delima; Hasibuan, Rosmidah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to determine the effectiveness of using TikTok social media as a biology learning media at SMA Negeri 1 Rantau Utara. This research uses a descriptive method with a quantitative approach, to get an objective picture of how much influence TikTok has in supporting the teaching and learning process, especially in biology subjects. Respondents of this study were 40 people from 10 classes XI SMA Negeri 1 Rantau Utara. The data collection techniques used in this study were observation, interview, and questionnaire. The research data were analyzed descriptively. The results showed that the use of TikTok in learning biology was quite effective, with the effectiveness level reaching 56.8%. This shows that more than half of the respondents feel that learning through TikTok provides benefits in understanding biology material. Thus, TikTok has the potential as an alternative learning media that can support the learning process of students in today's digital era. The utilization of social media such as TikTok in education can be a relevant innovation to answer the challenges of 21st century learning.